Unknowing fanaticism : Reformation literatures of self-annihilation - Lerner, Ross (Fordham University Press, 2019)
We may think we know what defines religious fanaticism: violent action undertaken with dogmatic certainty. But the term 'fanatic, ' from the European Reformation to today, has never been a stable term. Then and now it has been reductively defined to justify state violence and to delegitimize alternative sources of authority. 'Unknowing Fanaticism' rejects the simplified binary of fanatical religion and rational politics and turns to Renaissance literature to demonstrate that fanaticism was integral to how both modern politics and poetics developed, from the German Peasant Revolts of the 1520s to the English Civil War in the mid-seventeenth century. This text traces two entangled approaches to fanaticism in the long Reformation: the targeting of it as a political threat and the engagement with it as an epistemological and poetic problem.